2023
DOI: 10.3390/nu15030775
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Recommendations for Table Tennis Players—A Narrative Review

Abstract: Table tennis (TT) is the second most popular racket sport globally and was the sixth most widely played Olympic sport in 2005. It is an indoor racket sport requiring a mixture of power, agility, alertness and fast reactions. Players need to move quickly around a table to receive the ball and produce powerful returns. New rules such as increased ball size and a change in ball material have changed the ball’s trajectory, increasing the overall duration and intensity of game play. Scientific research on TT is gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…It is unclear whether current screening policies and screening tools sufficiently meet current needs for a more preventive approach to tackle malnutrition. Also, dietitians have reported that malnourished individuals are referred too late [6]. It has been hypothesized that earlier detection and interventions addressing risk factors for malnutrition may have a positive effect on nutritional status or even prevent malnutrition, at least in some individuals [7 && ,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether current screening policies and screening tools sufficiently meet current needs for a more preventive approach to tackle malnutrition. Also, dietitians have reported that malnourished individuals are referred too late [6]. It has been hypothesized that earlier detection and interventions addressing risk factors for malnutrition may have a positive effect on nutritional status or even prevent malnutrition, at least in some individuals [7 && ,8].…”
Section: Introductionmentioning
confidence: 99%
“…This can be of paramount importance, seeing as an excess of exercise can have a negative effect on immunity [20]. Observations such as these lead to the development of recommendations regarding the monitoring of the vitamin D level in athletes, adjusting lifestyle and diet, and even supplementation if required [21][22][23].…”
Section: Introductionmentioning
confidence: 99%